WONCA 2015 preconference exchange: Self-discovery, friendship, and innovation amidst diversity and uncertainty - (:unkn) unknown (My University, 2016)
This commentary is the result of a long-distance creative writing project between young general practitioners (GPs) from around the world. They wrote this after participating in an exchange program in Turkey, where they had the opportunity to shadow a Turkish GP, and talk about primary health care around the world. This program was organized by the Vasco da Gama Movement (Vasco da Gama Movement is WONCA Europe's Working group for New and Future GPs: http://vdgm.woncaeurope.org/).
Keywords: Turkey; Fear; friends; general practitioners